The Effect of Supercritical CO2 on Shaly Caprocks - Hadian, Pooya (Curtin University, 2020)
The effect of interactions between CO2, brine, and minerals constituting the caprock, have a significant influence on the effectiveness of the caprock sealing properties. In this study, shale samples were exposed to supercritical CO2 at in-situ pressure, temperature, and salinity condition, representative of a CO2 storage operation in Southwest Hub, Western Australia. Mineralogical and petrophysical properties of the samples are analysed with several experimental methods accompanied with reaction path modelling to track the changes after exposure of samples to CO2.